2017
DOI: 10.1108/yc-11-2016-00647
|View full text |Cite
|
Sign up to set email alerts
|

Typology of measures of children engagement in parental purchase decisions

Abstract: Purpose Although there is a common agreement that children participate and impact parental purchase decisions, the research results are rather inconsistent. One of the reasons for the differences in the findings could be attributable to different operationalisations of a child engagement variable in surveys. This study aims to classify the instruments used to measure children engagement in parental purchase decisions and to develop a typology of these instruments. Design/methodology/approach In total, 67 art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…The role of children in family purchases might range from cases where a child does not participate at all to fully autonomous decisions of a child; however, in many cases, a child’s role means only his or her participation in certain stages of the process or their ability to influence parents’ decision (Dikcius et al, 2017). Both of the extremes (decision made by either only parents or only by a child) mean entirely autonomous decisions that exclude the participation and influence of other family members, only partially belongs to the research domain that concentrates on family decision making.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…The role of children in family purchases might range from cases where a child does not participate at all to fully autonomous decisions of a child; however, in many cases, a child’s role means only his or her participation in certain stages of the process or their ability to influence parents’ decision (Dikcius et al, 2017). Both of the extremes (decision made by either only parents or only by a child) mean entirely autonomous decisions that exclude the participation and influence of other family members, only partially belongs to the research domain that concentrates on family decision making.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Researchers have used numerous scales and items/questions for measuring children’s participation or their influence in parental purchase decisions. Dikcius et al (2017) identified more than 80 research instruments in use; however, the majority of the scales have been developed ad hoc and tested deploying only relatively simple procedures of reliability tests (exploratory factor analysis [EFA], Cronbach’s alpha) or even measured participation/influence with only one item. The range of used measures starts from the direct statements evaluated on a Likert-type scale or listed options, for example, “When my child uses this (pestering technique), I tend to yield (purchase)” (Shoham & Dalakas, 2006) or “Teen played a role in your decision to get him or her vaccinated or not to get him or her (vaccinated)” (Dorell, Yankey, Kennedy, & Stokley, 2013).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations